Deep autoencoders for unsupervised anomaly detection in wildfire prediction - Üstek, İrem; Arana-Catania, Miguel; Farr, Alexander; Petrunin, Ivan (American Geophysical Union (AGU), 2024)
Wildfires pose a significantly increasing hazard to global ecosystems due to the climate crisis. Due to its complex nature, there is an urgent need for innovative approaches to wildfire prediction, such as machine learning. This research took a unique approach, differentiating from classical supervised learning, and addressed the gap in unsupervised wildfire prediction using autoencoders and clustering techniques for anomaly detection. Historical weather and normalized difference vegetation index data sets of Australia for 2005–2021 were utilized. Two main unsupervised approaches were analyzed. The first used a deep autoencoder to obtain latent features, which were then fed into clustering models, isolation forest, local outlier factor and one‐class support vector machines for anomaly detection. The second approach used a deep autoencoder to reconstruct the input data and use reconstruction errors to identify anomalies. Long Short‐Term Memory autoencoders and fully connected (FC) autoencoders were employed in this part, both in an unsupervised way learning only from nominal data. The FC autoencoder outperformed its counterparts, achieving an accuracy of 0.71, an F1‐score of 0.74, and an MCC of 0.42. These findings highlight the practicality of this method, as it effectively predicts wildfires in the absence of ground truth, utilizing an unsupervised learning technique.
Keywords: 37 Earth Sciences; 41 Environmental Sciences; 51 Physical Sciences; Machine Learning and Artificial Intelligence